The Effect of Physical Education Instructional Media on Long Jump Learning Outcomes - Ritonga, Doris Apriani; Verawati, Indah; Damanik, Saipul Ambri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This research aims to see the effect of the use video on physical Education learning outcomes for state high school students in Medan City. The method used in this research is an experimental method using the Pre Experimental Design research type. The sample in this research was state high school students in Medan City, totaling 25 students. Data analysis in this study used SPSS (version 25). The results of this research show that the data normality test shows that the pretest and posttest significance values ​​are greater than 0.05, so it can be concluded that the data is normally distributed. The significance value homogeneity test is greater than 0.05, so it can be concluded that the data is homogeneously distributed. The T test between the pretest and posttest output of the